SATB2 Defect Promotes Colitis and Colitis-associated Colorectal Cancer by Impairing Cl-/HCO3- Exchange and Homeostasis of Gut Microbiota. (21st May 2021) - Ni, Hengli; Chen, Yongyu; Xia, Wei; Wang, Chuyi; Hu, Caihong; Sun, Lina; Tang, Wen; Cui, Hongxia; Shen, Tong; Liu, Yao; Li, Jianming
Abstract: Background: SATB2 is a diagnostic biomarker and a favourable prognostic marker for colorectal cancer [CRC], but its role in colitis and colitis-associated colorectal cancer [CAC] is unknown. Methods: Colitis was induced in intestinal epithelial-specific Satb2 knockout [Satb2 IEC-KO] and control mice using dextran sulphate sodium [DSS]. RNA-seq analysis was performed on colonic tissues, and 16S rDNA-Seq on faecal bacterial DNA from Satb2 IEC-KO and control mice. Immunohistochemistry and flow cytometry were performed to reveal the proportions of different immune cells. Chromatin immunoprecipitation [ChIP] and luciferase reporter were applied to show the regulatory role of SATB2 on SLC26A3, of which the Cl - /HCO3 - exchange activity was measured fluorometrically by the pHi-sensitive dye. Bacteroides were detected by fluorescence in situ hybridisation [FISH] on colonic tissue. Results: Satb2 IEC-KO mice suffered from intestinal epithelial damage spontaneously, and developed more severe colitis and CAC. The expression of SLC26A3 correlated well with SATB2 revealed by RNA-seq and The Cancer Genome Atlas [TCGA] data, and was governed by SATB2 confirmed by ChIP and luciferase reporter experiments. Decreased intestinal flora diversity was seen in Satb2 IEC-KO mice. Bacteroides were more abundant and could colonise into the inner layer of colonic mucosa in Satb2 IEC-KO mice. Faecal microbiome transplantation from Satb2 IEC-KO mice aggravated colitis and M1 macrophages infiltration. Conclusions: SATB2 plays a vital role in maintaining intestinal homeostasis, and its deficiency promotes the development of colitis and CAC by influencing the intestinal luminal environment and gut flora. Graphical Abstract: